ASSESSMENT OF OCCUPATIONAL PROFILE AND TIME UTILIZATION PATTERN OF FRESH AND DRY FISH RETAILERS AND LABOURERS IN DAKSHINA KANNADA, KARNATAKA - V., Reena; Sharma, Arpita; Sharma, Rama; Singh, Ram; Landge, Asha T (Journal of Indian Fisheries Association, 2011)
The contribution of women in fisheries is substantial. Women are involved in productive activities directly related to fisheries production, processing and marketing as well as in non-fisheries livelihood activities that are very important in augmenting household income during periods of scarcity and seasonality often experienced by fishing communities. A study was conducted with the objective of assessing the occupational profile of fresh fish retailers and labourers in Dakshina Kannada, Karnataka along with their time utilization pattern. Fisherwomen were mainly involved in four kinds of occupations namely ‘fresh fish retailers’, ‘dry fish retailers’, ‘fresh fish labourers’ and ‘dry fish labourers’. A total of 120 fisherwomen from 3 fishing villages Ullal, Bengre and Bolar of Dakshina Kannada constituted the sample for the study using stratified random sampling and data was collected with semi-structured interview schedule. The data collected from respondents were scored, tabulated and analyzed using suitable statistical methods. SPSS 10.1 was used for analyzing suitable data by one was ANOVA, and Duncan’s Multiple Range Test (DMRT) was used to see the significant difference between the means. Study has revealed that occupational profile of the members may appear to be homogeneous with fisherwomen being part of the group but there is a difference in the occupational structure, time utilization pattern, income and expenditure pattern. Due to heterogeneity in occupational profile of members of SHGs they are not taking up any group enterprise. Key words: Fisherwomen, Time study, Occupation.